2014
DOI: 10.1002/sec.1110
|View full text |Cite
|
Sign up to set email alerts
|

Right translated AES gray S‐boxes

Abstract: This article deals with an algorithm for the generation of impregnable substitution boxes (S-box). The proposed scheme involves the application of right translation and Gray codes over the original Advanced Encryption Standard (AES) S-box. Regular representation of Galois field GF(2 8 ) is used to produce the translational effect in the AES S-box. The translated AES S-box is then subjected to Gray codes for the enhancement in their algebraic complexity. The proposed scheme results 256 different cryptographical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…The algebraic based construction of S-boxes has been rigorously investigated in literature [49][50][51][52]. The second half of the proposed hybrid method involves the algebraic group based cryptographic features improvisation of Sboxes generated in previous section III.A.…”
Section: B Proposed Group Structures and Actionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The algebraic based construction of S-boxes has been rigorously investigated in literature [49][50][51][52]. The second half of the proposed hybrid method involves the algebraic group based cryptographic features improvisation of Sboxes generated in previous section III.A.…”
Section: B Proposed Group Structures and Actionsmentioning
confidence: 99%
“…Hence, through bijection from I Ωi to A 1 , we get S-box S 1 which is shown in Table 6. The finite group G 6 =<x, y, z: x:= (1,38,17,51) y:= (2,48,18,57,30,61,41,32,44,22,35,43,34,62,11,16,58,37,53,10,46,47,29,45,24,56,20,8,6 on the index set of A 2 generates a distinct S-box. After thorough analysis and research, it has been revealed that the S-box related to the element x 3 y 47 z 5 ϵ G 6 offers the highest average value of non-linearity.…”
Section: B Proposed Group Structures and Actionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of the 256‐bit protection an initial 256‐bit long key is extended to required 240 bytes. Plaintext or an initialization vector is copied into a 4 x 4 byte matrix called State . Then, State matrix is mixed during the initial round with bytes of the extended key.…”
Section: The Basic Ideamentioning
confidence: 99%
“…The newly generated S-boxes have high resistance against linear and differential attacks. Khan and Azam [12] proposed a method for the construction of multiple S-boxes based on a group action and Gray codes. Similarly, Khan and Azam [13] presented another algorithm for the design of S-boxes based on affine and power mappings.…”
Section: Introductionmentioning
confidence: 99%